Islamic entrepreneurship in the light of maqasid al-shari’ah: a critical review - Mohammed Shehu, Farida; Al-Aidaros, Al-Hasan (2015)
The objectives of entrepreneurship in Islam are guided by the Maqasid Al-Shariah.However, there is a mismatch between Islamic entrepreneurship objectives and Maqasid Al-Shariah based on available literatures, which have not been critically investigated.This paper presents a critical review of the literature within the Islamic entrepreneurship objectives and Maqasid Al-Shariah framework.The exploratory study adopting content analysis to achieve its aim found that the existing literature covered both the Din and Mu’amalah based objectives of Islamic entrepreneurship.However, there is dearth of literature that integrates the connection between objectives of Islamic entrepreneurship and Maqasid Al-Shari’ah.It is therefore suggested that researchers should conduct more researches to examine the integration of Maqasid Al-Shariah in Islamic entrepreneurship, particularly in respect to decision making in handling entrepreneurship issues.